Commuting distances to local non‐farm workplaces and out‐migration: The case of Northeast Thailand. (9th October 2019) - Shirai, Yuko; Leisz, Stephen; Fox, Jefferson; Rambo, A. Terry
Abstract : The relationship between commuting distances and where people work has been studied for urban contexts in both developed countries and developing countries. However, few studies have examined the situation in rural areas, and none look at commuting distances to non‐farm workplaces in rural areas of developing countries. This paper investigates how commuting distance, and thus accessibility, to local non‐farm work influences non‐farm employment and out‐migration from rural villages in Northeast Thailand. The main issues examined are: (i) the distance that rural residents travel to work in local non‐farm jobs; and (ii) the influence that local non‐farm employment has on the number of outmigrants from rural villages. The study finds: (i) distance between villages and non‐farm work sites impact the number of villagers who are employed in regular wage work; (ii) beyond 20 km villagers are less likely to travel to non‐farm employment using their own means of transportation; and (iii) employment in regular wage work decreases outmigration. The findings from this study contribute to the debates over the drivers of rural out‐migration, rural livelihood changes, and agrarian changes that are taking place in Southeast Asia.